Spiritualitas untuk Pemulihan Pecandu Napza: Sebuah Eksplorasi berdasarkan Lukas 15:11-32 - Jusuf, Yung Sutrisno (Faculty of Philosophy, Parahyangan Catholic University, Bandung, 2021)
The longing of every sinner is to return to the right path. A sinner wants forgiveness and mercy. In the spiritual context, drug addiction is a form of sin that destroys human relationship with God. Drug addicts are victims of human failure to control their desires and thus they suffer and lose their dignity. To return to normal life and regain his or her dignity, a drug addict must follow a rehabilitation process. A therapeutic community for drug addicts is a rehabilitation model that involves the role of others in the recovery process. The atmosphere of community life, fraternity, and togetherness is built in this community so that each person can feel wholeness as dignified and loving human being. A therapeutic community needs a model of spirituality to achieve the aspired values. This article explores the parable of Prodigal Son in Luke 15:11-32 to inspire a model of spirituality that can be used in a rehabilitation community for drug addicts, namely, the spirituality of compassion and mercy. In the spirituality of compassion and mercy, a drug addict is readmitted to the community to restore his or her dignity.